PENINGKATAN KETERAMPILAN MENULIS LAPORAN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW SISWA KELAS VIII-2 MTSN MODEL KUOK KOTA BANGKINANG - Diastuti, Indah Mei (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2016)
The purpose of the result is to explain the increasement and result of report writing and what factors affecting report writing skill through cooperative learning models specifically jigsaw. This research was being held in the form of Classroom Action Research that was divided into two cycles. Each cycle has two meetings. The qualitative data are observation sheet for student, teacher and field. The result of the research shows that there was increasement on students’ studying result in the beginning test is 17,85%. From 28 students, 5 students is complete and 23 students is incomplete. Then, there was 35,71% increasement in cycle I. From 28 students, there was 10 students ar incomplete and 18 students are complete. In cycle II, there was increasement 96,46%, from 28 students, there was 27 students are complete and 1 students is incomplete. Based on the result, it can be concluded that cooperative learning model specially jigsaw can increase the students’ interest affecting the increasement of students’ report writing skill. Keywords: cooperative, Jigsaw, increasement, writing, and report.